Coping, social support and information in patients with pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension: A 2-year retrospective cohort study - Bodil Ivarsson (SAGE Open Medicine, 2018)
Objectives: Pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension are severe diseases with complicated treatment that need care at specialist clinics. The aim was to investigate changes in the patients’ perceptions on coping, social support and received information when attending a newly started nurse-coordinated pulmonary arterial hypertension-outpatient clinic. Methods: The present study was a descriptive, questionnaire-based cohort study including 42 adult patients. To evaluate coping, the Pearlin Mastery Scale was used. Social support, information and health-related quality of life were measured using Social Network and Support Scale, QLQ-INFO25 and the EQ-5D. Results: Attending the pulmonary arterial hypertension-outpatient clinic increased coping ability (Mastery Scale) significantly (baseline 16.0 ± 3.3 points vs 2-year follow-up 19.6 ± 5.2 points, p < 0.001) while there was no difference in social network and support or in perception of received information after. Patients who improved their coping ability (67%) were younger, had better exercise capacity, experienced better health-related quality of life and were more satisfied with received information about treatment and medical tests than those who reduced the coping ability. There was no difference in gender, diagnosis, time since diagnose, pulmonary arterial hypertension–specific treatment, education level or civil status between the two groups. Conclusion: This study suggests that the pulmonary arterial hypertension-team, in partnership with the patient, can support patients to take control of their disease and increase their health-related quality of life.